2004
DOI: 10.5558/tfc80341-3
|View full text |Cite
|
Sign up to set email alerts
|

An ecological rationale for sustainable forest management concepts at Riverside Forest Products, southcentral British Columbia

Abstract: Riverside Forest Products (Kelowna, British Columbia) has embraced a sustainable forest management approach for the management of one its forest tenures-Tree Farm License 49. This document discusses the rationale behind many of the concepts within this approach in the context of current ecological theory. We focus specifically on the following concepts: (1) forest retention, (2) ecosystem representation, (3) ecological contributions from unharvested forests, (4) zoning and the TRIAD approach, (5) stand-level h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
(35 reference statements)
0
5
0
2
Order By: Relevance
“…This was before the TRIAD concept had been fully developed, but it was nonetheless in keeping with the concept of the 3 zones. In the early 2000s, Riverside Forest Products planned to apply the TRIAD zoning concept to a 145 000-ha Tree Farm License (TFL 49) near Kelowna, British Columbia, and funded research to decide how best to divide the landscape (D'Eon et al 2004). Based on an analysis of vulnerability to climate change and potential for timber production, Nitschke and Innes (2008) recommended setting aside 17% of the landscape for conservation, 34% for intensive management, and 49% for extensive management.…”
Section: What Is the Triad Approach To Forest Management?mentioning
confidence: 99%
“…This was before the TRIAD concept had been fully developed, but it was nonetheless in keeping with the concept of the 3 zones. In the early 2000s, Riverside Forest Products planned to apply the TRIAD zoning concept to a 145 000-ha Tree Farm License (TFL 49) near Kelowna, British Columbia, and funded research to decide how best to divide the landscape (D'Eon et al 2004). Based on an analysis of vulnerability to climate change and potential for timber production, Nitschke and Innes (2008) recommended setting aside 17% of the landscape for conservation, 34% for intensive management, and 49% for extensive management.…”
Section: What Is the Triad Approach To Forest Management?mentioning
confidence: 99%
“…planning processes to introduce TRIAD zonation into their tenures (e.g., Boyland et al 2004, D'Eon et al 2004. Internationally, it is widely assumed that much of the future global demand for wood can and should be met from tree plantations managed with varying degrees of intensity (Matthews andHammond 1999, Bazett 2000).…”
Section: Term Acronym Silvicultural Activities Rotationmentioning
confidence: 99%
“…Pilot projects on intensification have been initiated (D'Eon et al 2004), but the future character and competitiveness of CIS/SIS-managed forests remains unclear. In our view, CIS/SIS managed Canadian forests will have the following characteristics: 1.…”
Section: A Cis/sis Strategy For Canadamentioning
confidence: 99%
“…It is therefore relatively easy to set aside large parts of this forest for extensive management, intensive management, and some conservation over the long term. Research indicating the possible benefits of such triad management has been carried out in several Canadian provinces (D'Eon et al 2004;Nitschke and Innes 2008;Messier et al 2009) and U.S. states (Seymour and Hunter 1992;Redelsheimer 1996), and it has even been suggested that such a system might be beneficial in Sweden (Ranius and Roberge 2011). On the other hand, triad management might not be as easily applied to more diverse forests or to privately owned forests managed at smaller spatial and temporal scales.…”
Section: Introductionmentioning
confidence: 96%